Plats och minne - Vännman, Marta (SLU/Landscape Architecture (until 121231), 2010)
Place as a concept, and memory as a phenomenon is researched through literature studies. The essay investigates how we think about place and how we experience and relate to it. Memory is discussed both as personal memory and collective memory.